“To Prevent Our Sverdlovsk Family of Byzantinologists from Falling to Pieces”: M. Ja. Sjuzjumov’s Letters to I. P. Medvedev - Tatiana Kushch (Античная древность и средние века, 2018)
This article publishes 25 letters from a prominent Soviet Byzantinist M. Ja. Sjuzjumov to his disciple, now famous Russian scholar I. P. Medvedev. These letters were written from 1967 to 1981. Letter no. 1 covers Medvedev’s first academic achievement, when his candidate’s dissertation was defended. The last message was sent out four months before Sjuzjumov’s death. These letters captured some fragments from lives of two Byzantologists, bound together by “scholarly friendship”. The correspondence mainly concentrates on the discussion of academic matters and the pride in a disciple’s achievements. This small epistolary corpus also reflects the history of development of the Ural School of Byzantine Studies, established by Sjuzjumov. The letters are published with an original preface and commentary.